Application of surface pressure measurements from O2-band differential absorption radar system in three-dimensional data assimilation on hurricane: Part I – An observing system simulation experiments study. (January 2015) - Min, Qilong; Gong, Wei; Lin, Bing; Hu, Yongxiang
Abstract: Sea level pressure (SLP) is an important variable in regulating hurricane motion. However, SLP generally cannot be measured in open oceans due to limited buoys. Because of the potential availability of an O2 -band differential absorption radar for sea surface barometry, we investigate the value of assimilating various patterns of SLP from such a system on hurricane prediction using the Weather Research and Forecasting (WRF) three-dimensional variational data assimilation system (3DVAR) based on Observing System Simulation Experiments (OSSEs). An important objective of this series of study is to explore the potential to use space and airborne sea surface air pressure measurements from an O2 -band differential absorption radar currently under development for server weather including hurricane forecasts. The surface pressure patterns include an area of SLP, and a band of SLP either through the center or tangent to the hurricane position; the latter two distributions are similar to what could be obtained from the differential absorption radar system, which could be installed on spaceborne satellites and/or mounted on reconnaissance aircraft. In the banded pressure cases, we propose a vortex reconstruction technique based on surface pressure field. Assimilating observations from the reconstructed surface pressure leads to a better representation of initial SLP and vertical cross-section of wind, relative to the control where no data is assimilated and to the assimilation without vortex reconstruction. In eight of the nine OSSEs simulations on three hurricanes with three leading times of integration, which cover a wide range of initial minimum SLP from 951 to 1011 hPa, substantial improvements are found not only in the hurricane track and position, but also in the hurricane intensity, in terms of the SLP and maximum surface wind. The only case without significant improvement is resulted from the very weak initial condition (SLP 1011 hPa), which had no clear indication of tropical disturbance at the stage for initialization. The improvements of assimilation are generally enhanced for the stronger hurricanes whose differences in initial minimum SLP between nature run and control are larger. Highlights: A novel O2 -band differential absorption radar for sea surface pressure. The potential applications of measured SLP for severe weather forecasting. A new vortex reconstruction scheme for SLP assimilation. The improvements of hurricane track and intensity with SLP assimilation. Evaluation of differential absorption radar system through OSSE assimilation.